PENGARUH KUALITAS LAYANAN DAN SERVICESCAPE RUMAH SAKIT TERHADAP KEPERCAYAAN KONSUMEN (STUDI PADA PASIEN POLIKLINIK RAWAT JALAN RUMAH SAKIT SILOAM BALI PADA PANDEMI COVID-19) - Dwi Setyawati; I Gusti Ngurah Agung Gede Eka Teja Kusuma; I Wayan Gede Antok Setiawan Jodi (VALUES, 2022)
Hospitals as health service providers must be able to provide the best quality of service to patients in order to increase patient’s trust when seeking treatment at the hospital. In addition to service quality, hospitals must also pay attention to the servicescape they have so that they can make patients feel confident when taking treatment. This study aims to examine the effect of service quality and servicescape on consumer trust. The research was conducted at the Outpatient Polyclinic of Siloam Hospital Bali. The sample of this study was 170 patients who received outpatient treatment. Sampling using the type of non-probability sampling using a formula (5 x Indicator). The method used is multiple linear regression analysis. The results of this study indicate that Service Quality has a positive and significant effect on Consumer Trust. And Servicescape has a positive and significant effect on Consumer Trust.